Solar charging controller using DC-DC buck converter with cascaded PI controller for a sustainable renewable energy system - Laksmi B., Nur Vidia; Muhammad Syahril Mubarok; Aribowo, Widi; Umaroh, Susi Tri; Ariyanto, Sudirman Rizki; Nurlita, Ita; Rahmadian, Reza (Sustinere: Journal of Environment and Sustainability, 2025)
The renewable energy system (RES) has recently become hot topic due to its unlimited, green energy potential, and the maturity of its technology. A solar charging controller (SCC) is required to regulate parameters for the battery and is an essential component for sustainable and renewable energy usage. An SCC based on a DC-DC Buck converter with cascaded proportional-integral (PI) controller is used in the system for managing the current and voltage loops, thereby preventing battery overcharging. The control parameters are determined using the Ziegler-Nichols method based on the reaction curve. A first -order system is employed due to the open-loop responses show no overshoot and oscillations. MATLAB software is used for both simulation and controller design. Simulations are conducted to validate the proposed SCC with the cascaded controller. Variations in the state of charge (SoC) are presented in two cases: without and with the controller. The SoC is set 20%, 50%, and 95%. A high SoC percentage indicates that the battery is near the full capacity, whereas a low percentage indicates that battery is near empty. Using the cascaded controller, both current and voltage responses at different SoC levels demonstrate satisfactory performance, including rapid transient responses, minimal overshoot, small ripples, and robustness.